2016
DOI: 10.1111/jvim.14526
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Diagnostic Imaging Features of Brain Herniation in Dogs and Cats

Abstract: BackgroundQuantification of brain herniation on MRI and its immediate clinical implications are poorly described.ObjectivesDefine the normal position of caudal fossa structures on brain MRIs in dogs and cats utilizing morphometry, compare this to dogs and cats with caudal transtentorial herniation (CTH), foramen magnum herniation (FMH) or both identified on MRI, and investigate associations between herniation severity, clinical signs, and 24‐hour outcome.AnimalsNinety‐two controls (66 dogs, 26 cats), 119 cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 16 publications
0
41
1
Order By: Relevance
“…The most common clinical signs were mental status alteration with confusion/disorientation or dulling, deficits of postural reactions, menace response, and cranial nerves. According to previous studies, clinical signs directly attributable to brain herniation were not always present . Circling and head pressing, related to small cysts involving the basal nuclei or the superficial cortex, and the frontal lobe respectively, were not observed in the population of our study .…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…The most common clinical signs were mental status alteration with confusion/disorientation or dulling, deficits of postural reactions, menace response, and cranial nerves. According to previous studies, clinical signs directly attributable to brain herniation were not always present . Circling and head pressing, related to small cysts involving the basal nuclei or the superficial cortex, and the frontal lobe respectively, were not observed in the population of our study .…”
Section: Discussioncontrasting
confidence: 55%
“…The Cushing reflex is more closely correlated with brainstem ischemia than high intracranial pressure, which limits the clinical usefulness of systemic hypertension as a specific indicator of high intracranial pressure . Several authors have reported a poor relationship between clinical signs and brain herniation in dogs . Mass effect, effacement of the cerebral sulci, perilesional edema, and brain herniation, all detectable by magnetic resonance imaging (MRI), are considered signs of presumed intracranial hypertension .…”
Section: Introductionmentioning
confidence: 99%
“…A recent study failed to show a directly attributable association between brain herniation and anaesthetic complications in dogs and cats. 23…”
Section: Discussionmentioning
confidence: 99%
“…Cerebellar herniation was measured on sagittal T2W image slices as previously described in canine and feline models (Fig. 4a, b) [42]. Nontreated animals with HMLS had a significant increase in caudal transtentorial herniation (p = 0.0284; Fig.…”
Section: Nsc Ev Treatment Inhibits Cerebellar Herniation With Increasmentioning
confidence: 93%
“…All foremen magnum and transtentorial herniation analysis was performed on midsagittal T2W MR images as described [42]. Briefly, bony landmarks were utilized to create three linear measurements: skull length line (SLL; Fig.…”
Section: Herniation Analysismentioning
confidence: 99%